Early Access in Oncology: Why Is It Needed?. (June 2019) - Apolone, Giovanni; Ardizzoni, Andrea; Buzzetti, Giuliano; Clerico, Mario Alberto; Conte, Pierfranco; de Braud, Filippo; De Lorenzo, Francesco; Ferrandina, Maria Gabriella; Genazzani, Armando; Gori, Stefania; Maio, Michele; Patroncini, Mauro; et al.
Timely access to cancer therapies with significant added value is an important expectation for patients and a primary responsibility for every public health service. Over time, collaboration between the pharmaceutical industry and regulatory agencies has made it possible to agree to implement tools in order to accelerate the development and approval of potentially innovative drugs. In Italy, too, several early access tools have been introduced. In June 2018 a panel of experts agreed on the need to simplify and streamline early access assessment criteria and processes. The panel developed a proposal to categorize cancer drugs eligible for early access. In the curative setting, the evaluation of the medical need should take into account both the relapse rate, attributed on the basis of the disease free survival (DFS), and the strength of the recommendations of the Italian Association of Medical Oncology (AIOM) for any therapeutic alternatives already available. The panel then found it appropriate to use the European Society for Medical Oncology (ESMO) criteria for the evaluation of the clinical benefit. The sum of the scores assigned to the three parameters should allow the clinical value of the drug to be defined and, consequently, the priorities for early access to be established. This multiparameter approach can also be adapted to the non-curative setting. The early access process should be reserved for first-in-class drugs and should provide for the recognition of a conditional reimbursement within 60 days, financed by a special fund. The proposal developed by the panel has the objective of starting a proactive discussion with the Italian health authority.